Rationale and design of the BRAVERY study (EPOC1701): a multicentre phase II study of eribulin in patients with BRAF V600E mutant metastatic colorectal cancer. Issue 6 (13th November 2019) - Masuishi, Toshiki; Taniguchi, Hiroya; Kotani, Daisuke; Bando, Hideaki; Komatsu, Yoshito; Shinozaki, Eiji; Nakajima, Takako Eguchi; Satoh, Taroh; Nishina, Tomohiro; Esaki, Taito; Wakabayashi, Masashi; Nomura, Shogo; et al.
Abstract : Background: BRAF V600E mutations are associated with aggressive biology and limited response to standard chemotherapy, especially during second-line and beyond therapies. BRAF V600E mutant and wild-type colorectal cancers (CRCs) differ in their expression profiles, and preclinical evidence suggests that microtubule inhibitors have an antitumour effect on xenograft models of BRAF V600E mutant CRCs. Eribulin has the best growth inhibitory activity in vitro of the microtubule inhibitors. Also, we have evidenced a hint of activity for patients with BRAF V600E mutant metastatic CRC (mCRC) with tumour shrinkage following eribulin treatment. Trial design: The BRAVERY study is a multicentre phase II study to evaluate the efficacy and safety of eribulin in patients with BRAF V600E mutant mCRC detected in either tumour tissues (primary analysis part) or circulating tumour DNA assays (liquid biopsy part). Key eligibility criteria are refractoriness and intolerance to at least one regimen (including irinotecan or oxaliplatin) containing fluoropyrimidine and Eastern Cooperative Oncology Group performance status of 0–1. Eribulin is to be administered intravenously at a dose of 1.4 mg/m 2 on days 1 and 8 and repeated every 21 days. The primary endpoint is the confirmed objective response rate (ORR) by investigator's assessment. We calculated the sample size of the primary analysis part at 27 patients using a two-stage design with 25% ORR deemed promising and 5% unacceptable (one-sided α, 0.05; β, 0.1). Secondary endpoints include disease control rate, progression-free survival, overall survival and adverse events. Moreover, we will collect pretreated tissue and serial blood samples for biomarker analyses, focusing on gene expression associated with BRAF mutant-like CRC to find predictive markers and acquired gene alterations to detect resistance mechanisms to eribulin. We initiated patient enrolment in March 2018, completed the primary analysis on May 2019, and are currently continuing with the liquid biopsy part. Trial registration number: UMIN000031221 and 000031552.